The Battīl and Zārūqah of Musandam, Oman. (9th March 2014) - Weismann, Norbert; Staples, Eric; Ghidoni, Alessandro; Vosmer, Tom; Dziamski, Piotr; Haar, Lilli
<x xml:space="preserve">Abstract</x> Most of the traditional boats still in use in Musandam, Oman, are essentially batātīl or zawārīq. Both types of vessel are described and compared in detail and placed within the larger context of boat types found in the surrounding region. This article attempts to establish a classification based primarily on shape, construction and decorative features, and provides names of individual components in both in Arabic and Kumzari.